Interaction of a relativistic electron beam with electromagnetic fields in azimuthally corrugated waveguide - Ognivenko, V.V. (Вопросы атомной науки и техники, 2018)
Interaction of a relativistic electron beam with electromagnetic fields in the cylindrical waveguide with the perfectly conducting and sinusoidally corrugated in azimuth wall is theoretically investigated. Influence of geometrical parameters of the waveguide on characteristics of propagating in it fields is investigated. Regarding the approximation of small corrugation, analytical dependences of growth rates and resonant frequencies from beam and waveguide parameters are defined. Теоретично досліджена взаємодія релятивістського електронного пучка з електромагнітними полями в циліндричному хвилеводі із синусоїдно-гофрованими по азимуту ідеально-провідними стінками. Досліджено вплив геометричних параметрів хвилеводу на характеристики хвиль. У наближенні малої глибини гофри визначені аналітичні залежності інкрементів нестійкостей і резонансні частоти від параметрів пучка та хвилеводу. Теоретически исследовано взаимодействие релятивистского электронного пучка с электромагнитными полями в цилиндрическом волноводе с синусоидально-гофрированными по азимуту идеально-проводящими стенками. Исследовано влияние геометрических параметров волновода на характеристики распространяющихся в нем волн. В приближении малой глубины гофра определены аналитические зависимости инкрементов неустойчивостей и резонансные частоты от параметров пучка и волновода.